Neuro-anesthetic Management of Craniotomy-surgery in Removal Tumor Multiple Meningioma Patients: A Case Report - Kulsum, Kulsum; Suryadi, Taufik (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The aim of following paper is to present the case anesthesia management of neuro-surgery in removal tumor multiple meningioma patients. METHODS: The method of this study was a case report. It was reported that a patient aged 50 years complained of spasms of full body spasms since 10 minutes before admission to the hospital. Complaints were accompanied by eyes glaring upward, seizure duration 20 minutes, after convulsions of unconscious patients, patients with previous tumor history, 3 years ago, patients with postoperative meningioma tumor removal. Patient diagnosed with multiple meningioma who planned to undergo craniotomy surgery to remove the tumor. MAIN FINDING: ASA 3 physical status with neurologic deficits. The patient is performed under general anesthesia with intubation. Induction performed by fentanyl, propofol and rocuronium. The operation lasted 3 hours. Postoperatively, the patient was admitted to the Intensive Care Unit for 2 days before moving into the room. Anesthetic treatment and regulation of physiological factors have a major impact on brain tissue. The anesthetist must have knowledge of the effects of drugs and other manipulations in order to achieve good surgical results. RESULT: Anesthetic management for meningioma cases has several special matters that are important to carry out. The brain tissue is covered by the cranium bone. Because of the continuous relationship of blood flow and brain tissue volume, the risk of bleeding and edema is very high. Without a proper anesthetic approach, it can increase the risk of edema and cerebral hemorrhage due to surgical manipulation.